Business process reengineering: Is it relevant to the Islamic banks? - Hasnan, Norlena (2017)
The emergence trends and the changing behavior of customers have led to the evolution of the Islamic finance. This has put high pressures for the Islamic banks to be competitive.The focus is no longer on cutting costs alone, but simultaneously improving services to customers. Owing to this fact, most banks have given special attention to the “processes” which able to produce values to the customers. One of the popular management tool, Business Process Reengineering (BPR), has been widely applied particularly in the manufacturing industries towards gaining significant improvement in organizational performances. Nevertheless, there is still lack of thorough empirical evidence of BPR impact on performance in Islamic bank services.It is still unsure whether BPR relevant and meaningful in enhancing the banks performance. Hence, this paper aims to explore the applications of the BPR factors in the Islamic banks and assess the effects towards the bank performance. Survey has been conducted on all banks and financial companies applied Islamic banking in Malaysia.The study received 65.6% feedback and successfully collected to be analyzed. . The overall result shows that the BPR factors and IT capability are able to influence overall performance of Islamic banking in Malaysia. However, for individually, the analysis using multiple regression analysis indicates that only Strategy alignment, Management Commitment, Information Technology (IT) Investment, Process redesign and Less Bureaucratic Structure have significant impact to performance of Islamic banking in Malaysia.The study provides meaningful insight for policy makers, banks practitioners and academicians on the bank performance enhancement.